Stretchable Supercapacitors as Emergent Energy Storage Units for Health Monitoring Bioelectronics. Issue 4 (10th December 2019) - Chen, Xue; Villa, Nicolo Simone; Zhuang, Yanfeng; Chen, Linzhe; Wang, Tianfu; Li, Zida; Kong, Tiantian
Abstract: Emerging health monitoring bioelectronics require energy storage units with improved stretchability, biocompatibility, and self‐charging capability. Stretchable supercapacitors hold great potential for such systems due to their superior specific capacitances, power densities, and tissue‐conforming properties, as compared to both batteries and conventional capacitors. Despite the rapid progress that has been made in supercapacitor research, practical applications in health monitoring bioelectronics have yet to be achieved, requiring innovations in materials, device configurations, and fabrications tailored for such applications. In this review, the progress in stretchable supercapacitor‐powered health monitoring bioelectronics is summarized and the required specifications of supercapacitors for different types of application settings with varying demands on biocompatibility are discussed, including nontouching wearables, skin‐touching wearables, skin‐conforming wearables, and implantables. The perspective of this review is then broadened to focus on integration of stretchable supercapacitors in bioelectronics and aspects of energy harvesting and sensing. Finally further insights on the existing challenges in this developing field and potential solutions are provided. Abstract : Stretchable supercapacitors as emergent energy storage units for health monitoring bioelectronics are reviewed. Progress and challenges associated with materials, design, and fabrication of stretchable supercapacitors in this application context are highlighted.